On the phase velocity in between weak and strong plasma edge turbulence. (11th June 2018) - Manz, P; Prisiazhniuk, D; Happel, T; Freethy, S; Hallatschek, K; Scott, B D; Stroth, U
Abstract: The influence of strong fluctuation levels on the phase velocity is studied just inside the last closed flux surface in the edge of magnetized confined plasmas by means of gyrofluid simulations. Linear features as growth rates and dispersion can be suppressed by small-scale vorticity generated by nonlinear self-sustainment. Measurements of the phase velocity by different diagnostic techniques could still provide finite values, which are not a result of linear instabilities, but are due to the nonlinear redistribution of spectral energy.